Peptic Ulcer of Esophagus - Tobalina, Juan B. (1963)
The digestive condition which most authors have addressed is probably the peptic ulcer. Very often we find publications about it , so that has become the most talked about of late disease spreading any all aspects that relate to it: its frequency, resulting in the production of statistics designed to show its increase in the general population , renewal in the therapeutic methods , and discussions on its etiology . These publications have taken to be a disease widely known by all physicians , whatever their specialty, feel able to diagnose and treat , since its suggestive symptoms and their therapy, a well-established pattern fits , facilitate its recognition and treatment. But all this almost always referred to their locations in the stomach and duodenum , forgetting that other segments of the gastrointestinal tract are likely to harbor the condition.